2015
DOI: 10.1016/j.jcrs.2014.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Vector analysis of astigmatism correction after toric intraocular lens implantation

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…These visual and refractive outcomes are consistent with recent studies of other toric IOLs. [5][6][7]14 Rotational stability is paramount in a toric IOL. Even minor degrees of misalignment can cause significant loss of cylinder correction efficacy with subsequent residual refractive errors and visual acuity deterioration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These visual and refractive outcomes are consistent with recent studies of other toric IOLs. [5][6][7]14 Rotational stability is paramount in a toric IOL. Even minor degrees of misalignment can cause significant loss of cylinder correction efficacy with subsequent residual refractive errors and visual acuity deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…These rotational stability results are similar to those reported in other recent toric IOL studies. [5][6][7]14 IOL rotation is mainly caused by haptic compression resulting from capsular contraction. The Precizon Toric IOL was designed with offset-shaped haptics to prevent postoperative rotation and posterior capsule opacification.…”
Section: Discussionmentioning
confidence: 99%
“…6 Several studies have reported successful visual and refractive outcomes after implantation of different model soft toric IOL. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The purpose of the current study is to report our clinical and visual outcomes at 1 month after uncomplicated cataract surgery with toric IOL implantation (SupraPhob).…”
mentioning
confidence: 99%
“…
We read with interest the paper by Krall et al 1 We found that the methods they followed to evaluate astigmatism correction by toric intraocular lenses (IOLs) might be optimized to obtain a more complete analysis of their results.First, the authors state that vectorial analysis was performed to determine the refractive astigmatic changes. The target induced astigmatism, surgically induced astigmatism, and difference vector were investigated using the Alpins method.
…”
mentioning
confidence: 99%
“…We read with interest the paper by Krall et al 1 We found that the methods they followed to evaluate astigmatism correction by toric intraocular lenses (IOLs) might be optimized to obtain a more complete analysis of their results.…”
mentioning
confidence: 99%